Graphene based electrode decorated with nanoparticles for detection of high priority trace heavy metals in aqueous solutions - Lee, Pui Mun (2016)
Water is essential to keep us to survive, but improper and careless treatment of the wastewater from industrialization may cause the release of heavy metals, such as Lead (Pb), Cadmium (Cd) and Copper (Cu) to water supply. These heavy metals may disrupt the supply chains and human health if the food and water were overdosed with heavy metals. Hence, detection of trace heavy metals in water is important for human health. The electroanalysis method was used with newly developed graphene-based working electrodes for the detection of trace heavy metals in aqueous solutions in this research due to their inexpensiveness, portability and sensitivity. In this project, two methods were used in the fabrication of the graphene-based electrodes. The first was an electrochemical method, with which drop-cast graphene oxide (GO) was electrochemically reduced to reduced graphene oxide (RGO). The electrochemical method was selected because it is simple and economic. In order to enhance the sensitivity of the electrodes, the electrochemically reduced RGO (ERGO) electrodes were decorated with tin nanoparticles (SnNPs). The second method was thermal reduction, where the drop-cast GO was thermally reduced to RGO at a high temperature. The thermal reduction method was chosen because it could potentially achieve large scale production. In addition, the thermally reduced RGO was further decorated with platinum (Pt) NPs to improve its sensitivity and selectivity towards the analytes (Cd2+, Pb2+ and Cu2+) in electroanalysis. In the characterization of the fabricated electrodes, several instruments, such as x-ray photoelectron spectroscopy (XPS), Raman spectroscopy, field emission scanning electron microscopy (FE-SEM) and energy dispersive x-ray spectroscopy (EDS) were been used. XPS was employed to investigate the reduction percentage of RGO by studying the carbon to oxygen (C/O) ratio. Raman spectroscopy was used to determine the graphitic structure of RGO by studying the D/G intensity ratio (ID/IG). FE-SEM was used to study the surface microstructure of the RGO based electrodes, while EDS was used to verify the elemental composition of metal NPs decorated RGO. In order to study the electrochemical behaviour of the electrodes, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed. The surface reversibility of the RGO based electrodes could be identified through CV, while the electron-transfer resistance (Ret) at the interface between electrodes and electrolytes could be determined through EIS. After that, several parameters, such as pH of buffer solution, pre-concentration potential and pre-concentration time, were systematically investigated to optimize the working conditions of the RGO-based electrodes during electroanalysis. Furthermore, the reproducibility, repeatability and storage stability of the prepared electrodes were also analyzed. After that, square wave anodic stripping voltammetry (SWASV) was performed to detect the analytes in aqueous solutions. Calibrations of the RGO-based electrodes were carried out to investigate the performance of the electrodes in electroanalysis, in terms of sensitivity, stability and selectivity. In addition, the limit of detection (LOD) of the analytes obtained from the electrodes was determined. Finally, real sample application was performed to justify the feasibility of the prepared RGO-based electrodes.